Co-benefits of soil carbon protection for invertebrate conservation - Flores-Rios, Angelli; Thomas, Evert; Peri, Pablo Luis; Amelung, Wulf; Duarte Guardia, Sandra; Borchard, Nils; Lizárraga Travaglini, Alfonso; Vélez Azañero, Armando; Sheil, Douglas; Tscharntke, Teja; Steffan-Dewenter, Ingolf; Ladd, Brenton (Elsevier, 2020)
The global decline in invertebrate diversity requires urgent conservation interventions. However, identifying priority conservation areas for invertebrates remains a significant challenge. We hypothesized that aligning the conservation of invertebrate biodiversity with climate change mitigation ofer offers a solution. As both soil carbon storage and invertebrate biodiversity are positively influenced by plant diversity and productivity, a positive correlation can also be expected between SOC and invertebrate biodiversity. Drawing on >10,000 invertebrate observations organized into functional groups, and site-specific soil organic Carbon (SOC) measurements from Patagonia, the Peruvian Andes, and montane tropical rainforest, we examined the role of climate, soil, topographical position and land use for prediction of invertebrate biodiversity. We found that taxonomic and functional invertebrate diversity and abundance closely correlate with SOC stocks within ecosystems. Topographical position of sites, which was partly associated with SOC, was also important, whereas land use was of subordinate importance. We conclude that recent advances in predicting and mapping SOC can guide the identification of habitats within landscapes with high biodiversity and conservation value for invertebrates. Our findings stress the importance of linking global climate change mitigation initiatives that aim to preserve and restore SOC to efforts aimed at improving the conservation of invertebrates and the ecosystem services they provide, for the realization of mutual climate and biodiversity benefits.